1996
DOI: 10.1097/00007632-199603150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Back Pain During Pregnancy

Abstract: Back pain during pregnancy is a common complaint. The 30% with the highest pain score reported great difficulties with normal activities. The back pain started early in pregnancy and increased over time. Young women had more pain than older women. Back pain starting during pregnancy may be a special entity and may have another origin than back pain not related to pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
270
4
37

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(339 citation statements)
references
References 12 publications
28
270
4
37
Order By: Relevance
“…These tests are also used in the present study, though they are named Palpation of the long dorsal ligaments and Pointing to the joint. Of the nine pain provocation tests Kristiansson et al [9] performed on the sacroiliac joints, the two most sensitive ones were Palpation of the symphysis and Painful femoral compression -in this study called Posterior pelvic pain provocation test. This 165 concords with the present study, where these two tests were among the five most sensitive.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…These tests are also used in the present study, though they are named Palpation of the long dorsal ligaments and Pointing to the joint. Of the nine pain provocation tests Kristiansson et al [9] performed on the sacroiliac joints, the two most sensitive ones were Palpation of the symphysis and Painful femoral compression -in this study called Posterior pelvic pain provocation test. This 165 concords with the present study, where these two tests were among the five most sensitive.…”
Section: Discussionmentioning
confidence: 86%
“…This 165 concords with the present study, where these two tests were among the five most sensitive. Pain provoking tests had a better inter-examiner reliability than that of topograpic/palpation tests, but as Kristiansson et al [9] showed, they also have a better specificity. This is also confirmed in the present study, which shows an almost identical specificity in the compression and separation tests.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…46 Additionally, patients with both LBP and PGP have been found to be at greatest risk of persistent pain postpartum 47 and to experience greater disability. 48 Although back pain spontaneously resolves postpartum for most, 49 those with persistent pain were more likely to have had back pain prior to pregnancy, present with early onset of symptoms, and exhibit higher pain severity during pregnancy. 50,51 Existing guidance on occupational lifting…”
Section: Occupational Lifting and Fetal-maternal Health Outcomesmentioning
confidence: 99%
“…Back pain is reported by as many as 50-76% of all pregnant women, generally as a musculoskeletal response to the shifting centre of gravity, weight gain and hormonal factors responsible for ligamentous relaxation and changes in the pelvic joints [99,165,170].…”
Section: Sciatica In Pregnancymentioning
confidence: 99%